Absolute recoil : towards a new foundation of dialectical materialism - Žižek, Slavoj (Verso, 2014)
"In this major new work the leading philosopher Slavoj Žižek argues that philosophical materialism has failed to meet the key scientific, theoretical and political challenges of the modern world, from relativity theory and quantum physics to Freudian psychoanalysis and the failure of twentieth-century Communism. To bring materialism up to date, Žižek proposes a new foundation for dialectical materialism. He argues that dialectical materialism is the only true philosophical inheritor of what Hegel designates as the speculative approach of thought - all other forms of materialism fail. In Absolute Recoil, Žižek offers a startling reformulation of the ground and possibilities of contemporary philosophy"--